Strategi Kepolisian Satuan Lalu Lintas Dalam Meningkatkan Ketertiban Berlalu Lintas Pada Kalangan Pelajar Remaja Di Kecamatan Kota Kefamenanu - Yohanes P M De Lourdes; Dimas Agustian; Detson Ray Halomoan Sitorus (Jurnal Administrasi Karya Dharma, 2026)
This study examines the strategies of the Traffic Police Unit (Sat Lantas) in improving traffic order among teenage students in Kefamenanu City. The high number of traffic violations by students, which include using vehicles without a driver's license (SIM), not wearing a helmet, and riding with more than one person, is the main background of this study. Data shows a fluctuating but still high trend of violations, as well as the emergence of fatal accidents involving students in 2023 and 2024. The Traffic Police Unit of the TTU Police has implemented various approaches including educational strategies through outreach to schools, preventive strategies through increased patrols, and repressive strategies in the form of firm action or tickets to provide a deterrent effect. This study aims to analyze the effectiveness of these steps using Mulgan's strategic governance theory approach which includes aspects of goals, environment, direction, action, and learning. The results of the study are expected to provide theoretical contributions to the science of public administration and practical benefits in increasing awareness and a culture of orderly traffic among the younger generation in Kefamenanu City.